High Stock Returns Before Holidays: Existence and Evidence on Possible Causes. - Ariel, Robert A (Journal of Finance, 1990)
On the trading day prior to holidays, stocks advance with disproportionate frequency and show high mean returns averaging nine to fourteen times the mean return for the remaining days of the year. Over one third of the total return accruing to the market portfolio over the 1963-82 period was earned on the eight trading days that fall before holiday market closings each year. Examination of hourly preholiday stock returns reveals high returns throughout the day. Preholiday stock returns in the posttest 1983-86 period are also examined.